Project Based Learning Model to Increase Students' Creativity in PAI Subjects at SMA N Kalirejo and Bangunrejo, Central Lampung Regency: Model Pembelajaran Project Based Learning untuk Meningkatkan Kreativitas Peserta Didik pada Mata Pelajaran PAI di SMA N Kalirejo dan Bangunrejo Kabupaten Lampung Tengah - Riadhus Sholihah; Septuri; Sunarto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Based Learning (PjBL) is a learning model designed to create innovative, student-centered learning by engaging students in solving problems through the creation of a product, making decisions, and conducting observations, thereby enhancing students’ creativity and motivation. The purpose of this research is to analyze and describe the implementation, outcomes, and challenges of the PjBL model in Islamic Education (PAI) subjects to improve students' creativity in Grade X at SMA Negeri Kalirejo and Bangunrejo. The research method used in this study is field research with a qualitative descriptive approach. Data collection techniques include in-depth interviews, participant observation, and documentation studies. The data analysis technique involves data reduction, data display, and conclusion drawing. Data validity is ensured through source triangulation. The results of this study indicate that the implementation of the PjBL model in PAI subjects to enhance students’ creativity in Grade X at SMA Negeri Kalirejo and Bangunrejo follows six steps according to the PjBL syntax: determining essential questions, designing project plans, scheduling, monitoring project progress, assessing results, and evaluating the experience. The PjBL model has proven effective in increasing student creativity in PAI subjects. The improvement in creativity is indicated by students showing high imagination, enthusiasm, increased confidence in expressing opinions, active participation in group work, and more controlled behavior due to collaborative learning. Challenges in implementing the PjBL model include limited time or the need for extended time, inadequate facilities and infrastructure, and a lack of conducive classroom environments.